IMPLEMENTATION OF LEGAL ASSISTANCE IN CRIMINAL CASES IN CIBINONG DISTRICT COURT - Radonna, Sutan Surya; Suprijatna, Dadang; Gilalo, J. Jopie (DERECHTSSTAAT, 2018)
Legal aid is a legal sevice program provided to alleviate the burden of life forÂ  people who cannot afford financially, and is also useful to create justice and legal protection to society. This legal research is an empirical legal research or descriptive field research. The research is located at Cibinong District Court. Data collection techniques were conducted through interviews with Cibinong District Court judges and literature studies in the form of books, legislation, journals, etc. to support comprehension and completeness of data or materials. Problems in this Research are about implementation of the granting of legal aid to defendants who cannot afford financially in criminal cases and restricted factors towards implementation of granting legal aid to defendants who cannot afford financially in criminal cases. Based on the research results, and the discussion about the analysis of the implementation of legal aid to defendants who cannot afford financially in criminal cases, the implementation of the granting of legal aid can be done through courts, and Legal Aid Institutes (LBH) andÂ  directly in accordance with initiative of advocates who voluntarily willing to accompany the defendants. Factors restricting implementation of granting legal aid to defendants who cannot afford financially in criminal cases such as: factors in law enforcement, social and cultural factors, facilities and infrastructure as well. As recommendation, it high required to to courts and LBH to socialize procedures of free legal assistance to the defendants and what sanctions to parties who inhibit the implementation of the granting of legal aid to the defendants in criminal cases.